A New Method to Protect Blood Supply in the Treatment of Femoral Neck Fractures: Bidirectional Compression Porous Tantalum Screws. Issue 9 (18th July 2022) - Zhao, Dewei; Ma, Zhijie; Liu, Baoyi; Yang, Lei; Qiu, Xing; Tian, Simiao; Okoye, Chukwuemeka Samuel; Lian, Zhiqiang
Abstract: Objective: To explore the clinical effect of a new type of bidirectional pressurized porous tantalum screw (PTS) internal fixation in treating femoral neck fractures (FNFs). Methods: In this study, geometric models of FNF were first established via reverse engineering method, followed by stimulation of the strength of PTSs in fixation of FNFs. A randomized control trial study was then conducted of 41 patients with FNF from October 2015 to December 2018. These patients included 12 males and 29 females with an average age of 59.9. The 41 patients were randomly divided into two groups: cannulated compression screws (CCSs) group ( n  = 21) and PTSs group ( n  = 20). Treatment outcomes in patients were evaluated using multiple imaging techniques, including X‐ray and digital subtraction angiography scanning as well as functional recovery Harris hip score. Without other postoperative complications, the primary outcome was defined as fracture healing after FNF internal fixation. Secondary outcomes are the incidence of the avascular necrosis of femoral head (ANFH), fracture nonunion, and reoperation rate. Results: Following PTS internal fixation of FNF, finite element results revealed a firmly fixed fracture with a slight displacement of less than 0.5 mm. At follow‐up, we found a statistically significant difference in Harris scores in the two groups at 1 month and 3 months post‐surgery. In the PTSs group, there was no case of ANFH and fracture nonunion, and the average healing time was 94.45 ± 6.47 days. In the CCSs group, there were four cases of ANFH, the necrosis rate was 19.05% (4/21). There was one case of fracture nonunion in the CCSs group, the nonunion fracture rate was 4.76% (1/21), and the average healing time was 122.54 ± 11.37 days. Five patients underwent total hip arthroplasty, and the reoperation rate was 23.81% (5/21). There were significant differences in the postoperative complications, fracture healing time, and reoperation rate between the two groups ( p  < 0.05). Conclusions: PTSs fixation of FNF at the center, does not only avoid the destruction of blood supply in the femoral head and reduction in the incidence of postoperative complications of FNFs, but also induces early bone ingrowth and promotes fracture healing. These findings provide a potential surgical internal fixation system for treating FNFs. Abstract : Cannulated compression screws internal fixation for femoral neck fractures can destroy the blood supply of the femoral head. The central fixation with tantalum metal screws can protect the femoral head epiphyseal arterial network and reduce postoperative complications.